2008
DOI: 10.3860/taper.v16i1.94
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate Supervision in the Philippines: Setting the Research Agenda

Abstract: This paper reviews the literature on postgraduate supervision by examining recent issues, approaches and perspectives. It highlights supervision as a professional practice where the supervisor is seen as one who must be a reflective practitioner. It also highlights strong intertwining between this field and the literature on professional practice. Elements of the supervisory process that take into consideration candidate-, supervisor-, and institutionrelated variables are proposed as areas for possible inquiry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…This situation could lead to a number of students failing to finish their degrees within the stipulated time or resorting to dropout. Despite the fact that supervisors need to lead candidates towards the successful completion of their theses (Calma 2007), some supervisors in our study were accused of not being available. The finding focussing on the lack of ethical consideration by some supervisors concurs with literature cited by Chireshe (2012) where some students claimed to be harassed by their supervisors.…”
Section: Discussion Of Findingsmentioning
confidence: 89%
See 1 more Smart Citation
“…This situation could lead to a number of students failing to finish their degrees within the stipulated time or resorting to dropout. Despite the fact that supervisors need to lead candidates towards the successful completion of their theses (Calma 2007), some supervisors in our study were accused of not being available. The finding focussing on the lack of ethical consideration by some supervisors concurs with literature cited by Chireshe (2012) where some students claimed to be harassed by their supervisors.…”
Section: Discussion Of Findingsmentioning
confidence: 89%
“…This situation can be ascribed to numerous factors such as inexperienced or overburdened supervisors, inadequate preparation of candidates, poor planning and management, methodological difficulties, personal problems outside research, insufficient financial support for students, poor relationship between student and supervisor, and overall ineffective infrastructural support for postgraduate studies (Bitzer 2011). Mapasela and Wilkinson (2005) and Calma (2007) found that the kind of supervision students receive is the most important of these factors. According to Frisch and Larson (2000), effective supervision of research students is acknowledged as a crucial factor in the student's successful completion of postgraduate study.…”
Section: Introductionmentioning
confidence: 99%
“…S/he exemplifies calm and patience, positive attitudes, approachability, constructive criticism, enthusiasm, commitment and dedication (Chikte & Chabilall, 2016). Supervisor should be expert in relevant study field (Calma, 2007;Sidhu, Kaur, Fook, & Yunus, 2014), topic expert , methodology expert, process expert, motivational expert (Polonsky & Waller, 2014) and should act as a confidence booster and motivator (Sidhu et al, 2014). Ali, Watson, and Dhingra (2016), explored the attitudes of supervisees and their supervisors towards supervision.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Calma ( 2007 ) points out that postgraduate supervision is a 'professional practice' and it is fast becoming an evolving fi eld of research interest not only among 'supervisors and candidates but also for other stakeholders who wish to examine it' (p. 91). Calma ( 2007 ) points out that postgraduate supervision is a 'professional practice' and it is fast becoming an evolving fi eld of research interest not only among 'supervisors and candidates but also for other stakeholders who wish to examine it' (p. 91).…”
Section: Literature Reviewmentioning
confidence: 99%